PENGARUH UKURAN PERUSAHAAN, LEVERAGE, ECONOMIC VALUE ADDED DAN RETURN ON INVESTMENT TERHADAP RETURN SAHAM - Noramita, Noramita; Hesty Ervianni Zulaecha; Hamdani, Hamdani; Seleman Hardy Yahawi (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The purpose of this study was to determine the effect of company size, leverage, economic value added and return on investment on stock returns in food and beverage companies listed on the Indonesia Stock Exchange (BEI). The research time periodused is 8 years, namely the 2014-2021 period. The study population includes food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2021 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 9 companies were obtained. The type of data used si secondary data obtained from the Indonesia Stock Exchange website and the official website of the sample companies. The analysis method used is panel data regression analysis. The results showed that company size had no effect on stock returns, Leverage had a positive effect on stock returns, Economic value added had no effect on stock returns, and Return on investment had an effect on stock returns.